Cryobiopsy in the diagnosis of diffuse interstitial lung disease: yield and cost-effectiveness analysis - Hernández-González, Fernanda; Lucena, Carmen M; Ramírez, José; Sánchez, Marcelo; Jimenez, María José; Xaubet, Antoni; Sellares, Jacobo; Agustí, Carlos (Archivos de bronconeumología (English ed.), 2015)
Assessment of patients with suspected interstitial lung disease (ILD) includes surgical lung biopsy (SLB) when clinical and radiological data are inconclusive. However, cryobiopsy is acquiring an important role in the ILD diagnostic process. The objective of this study was to evaluate the diagnostic yield, safety and economic costs of the systematic use of cryobiopsy in the assessment of patients with suspected ILD. This was a retrospective observational study of patients who had undergone transbronchial cryobiopsy for evaluation of ILD from January 2011 to January 2014. The procedures were performed with a video bronchoscope using a cryoprobe for the collection of lung parenchyma specimens, which were analyzed by pathologists. Diagnostic yield, complications and economic costs of this technique were analyzed. Criobiopsy specimens from a total of 33 patients were included. A specific diagnosis was obtained in 26, producing a diagnostic yield of 79%. In 5 patients, SLB was required for a histopathological confirmation of disease, but the procedure could not be performed in 4, due to severe comorbidities. The most frequent complications were pneumothorax (12%) and gradei (9%) or gradeii (21%) bleeding. There were no life-threatening complications. The systematic use of cryobiopsy saved up to €59,846. Cryobiopsy is a safe and potentially useful technique in the diagnostic assessment of patients with ILD. Furthermore, the systematic use of cryobiopsy has an important economic impact.